A Study on the Relationships Among Personality Traits, Gender and Customer Knowledge Preferences - Tseng, Shu-Mei; Liang, Chau-Wei; Tsai, Hsien-Lein (International Journal for Applied Information Management, 2022)
Empirical evidence suggests that an enterprise can obtain knowledge related to new demands about products or services through interactions with customers, which can be helpful references leading to the enhancement of customer satisfaction and loyalty. However, little is known about the antecedents of customer knowledge preferences. Therefore, this study begins with a literature review followed by the use of a questionnaire method to investigate the relationships among personality traits, gender and customer knowledge preferences. Results indicate that three of the five personality traits, as measured by the Big-5 factors of personality, contribute to explain customer knowledge preferences. Gender has a moderating effect on the traits of emotional stability and customer knowledge preferences.